Entwining polymer chains enables strong, flexible, and super-transparent radiative coolers with low environmental impacts for foldable photovoltaics - Xinyi Tian; Feiyang Xie; Yurong Pan; Yunjie Yang; Chengling Wang; Xuanhao Zhuo; Qianyi Yao; Chenyang Cai; Changlei Xia (Chemical Engineering Journal, 2026)

Fermented wheat germ attenuates metabolic dysregulation in offspring induced by maternal high-fat diet: insights from multi-omics analyses - Xiaolin Li; Yingyu Zhao; Aimei Liao; Long Pan; Yurong Xing; Jingjing Cheng; Jin Liu; Jihong Huang (Food Bioscience, 2026)

Fixed-mesh isogeometric analysis for phreatic surface reconstruction in 2D steady-state seepage flow - Quansheng Zang; Yunmu Zhou; Kunpeng Yuan; Ranran Li; Changyi Yu; Yurong Zhang; Yanhui Pan; Yongli Chen (Computers and Geotechnics, 2026)

Spatial and temporal evolution of wetland ecological quality in the Yellow River Delta: a comprehensive analysis based on multi-temporal remote sensing and improved ecological indices - Ruifeng Liu; Lansong Lv; Yurong Cui; Wenxin Pan; Xiulong Zhang; Juan Fu (Advances in Space Research, 2026)

Molecular insights into the stability of CO2 hydrate in variable-diameter nano-slit - Xu Li; Han Jia; Qiuxia Wang; Yuanbo Wang; Fangning Fan; Bowen Wang; Qiang Wang; Yurong Zhao; Pan Huang (Gas Science and Engineering, 2025)

ITZO/Ga2O3 heterostructure memristor with integrated optoelectronic synaptic function for neuromorphic vision applications - Yonghui Lin; Lun Zhong; Lu Wang; Yuxuan Nie; Fupeng Yang; Jianyong Pan; Yurong Liu; Ruohe Yao; Yang Li; Kuiwei Geng (Chemical Engineering Journal, 2025)

Curved Fe-N4 sites endows effective oxygen reduction reaction in acid medium - Yalin Liu; Gai Li; Min Chen; Yurong Liu; Tianyu Qiu; Xingqi Han; Jing Li; Ruisong Li; Xiaodong Shi; Zhenye Kang; Qinhe Pan; Xinlong Tian; et al. (Chemical Engineering Journal, 2025)

Rhubarb with Different Cooking Methods Restored the Gut Microbiota Dysbiosis and SCFAs in Ischemic Stroke Mice - Jing Xu; Taotao Liu; Fuzhu Pan; Xuan Ao; Lan Wang; Rixin Liang; Yuxin Lei; Yurong Ding; Miao Yu; Li Li; Hongjun Yang (Molecular Neurobiology, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Heat rectification effect enables all-season thermal management-electricity cogeneration using dual-mode metawood bricks with aligned semi-pores design - Xiaodan Wu; Jing Liu; Siying Guo; Xin Zhao; Yunjie Yang; Yurong Pan; Fulin Cheng; Yi Chen; Yibo Wang; Zechang Wei; Chenyang Cai; Wenbo Chen (Chemical Engineering Journal, 2025)

Transformative effects of homo-valence ion doping on persistent luminescence nanophosphors for radiotherapy monitoring - Ziyun Miao; Pei Xu; Yurong Wei; Jiahui Tan; Zhenwei Liu; Jie Pan; Lin Shi; Yong Wang; Jie Wang (Chemical Engineering Journal, 2025)

High-pressure homogenous extraction of thinned young apple polyphenol and its preservation effect on fresh pork - Yuqian Pan; Caiping Zhu; Biqi Du; Yifan Zhang; Chu Liu; Yurong Guo (Food Control, 2025)

Understanding the factors influencing high-temperature Daqu from different geographical regions - Zhendong Zhang; Yaolan Meng; Yurong Wang; Qiangchuan Hou; Haibo Zhang; Ming Zhang; Ge Hu; Yingying Zhou; Qifu Pan; Zhuang Guo (Food Bioscience, 2024)

Deciphering microbiomes dozens of meters under our feet and their edaphoclimatic and spatial drivers - Haoran He; Jingxiong Zhou; Yunqiang Wang; Shuo Jiao; Xun Qian; Yurong Liu; Ji Liu; Ji Chen; Manuel Delgado‐Baquerizo; Albert C. Brangarí; Li Chen; Yongxing Cui; et al. (Global Change Biology, 2024)
Microbes inhabiting deep soil layers are known to be different from their counterpart in topsoil yet remain under investigation in terms of their structure, function, and how their diversity is shaped. The microbiome of deep soils (>1 m) is expected to be relatively stable and highly independent from climatic conditions. Much less is known, however, on how these microbial communities vary along climate gradients. Here, we used amplicon sequencing to investigate bacteria, archaea, and fungi along fifteen 18‐m depth profiles at 20–50‐cm intervals across contrasting aridity conditions in semi‐arid forest ecosystems of China's Loess Plateau. Our results showed that bacterial and fungal α diversity and bacterial and archaeal community similarity declined dramatically in topsoil and remained relatively stable in deep soil. Nevertheless, deep soil microbiome still showed the functional potential of N cycling, plant‐derived organic matter degradation, resource exchange, and water coordination. The deep soil microbiome had closer taxa–taxa and bacteria–fungi associations and more influence of dispersal limitation than topsoil microbiome. Geographic distance was more influential in deep soil bacteria and archaea than in topsoil. We further showed that aridity was negatively correlated with deep‐soil archaeal and fungal richness, archaeal community similarity, relative abundance of plant saprotroph, and bacteria–fungi associations, but increased the relative abundance of aerobic ammonia oxidation, manganese oxidation, and arbuscular mycorrhizal in the deep soils. Root depth, complexity, soil volumetric moisture, and clay play bridging roles in the indirect effects of aridity on microbes in deep soils. Our work indicates that, even microbial communities and nutrient cycling in deep soil are susceptible to changes in water availability, with consequences for understanding the sustainability of dryland ecosystems and the whole‐soil in response to aridification. Moreover, we propose that neglecting soil depth may underestimate the role of soil moisture in dryland ecosystems under future climate scenarios.

Effects of anthropogenic emissions and meteorological conditions on diurnal variation of formaldehyde (HCHO) in the Yangtze River Delta, China - Yurong Gao; Hao Pan; Le Cao; Chunsong Lu; Qingjian Yang; Xichang Lu; Hongyi Ding; Simeng Li; Tianliang Zhao (Atmospheric Pollution Research, 2023)

Role of Elevated Thrombospondin-1 in Kainic Acid-Induced Status Epilepticus - Yurong Zhang; Mengdi Zhang; Wei Zhu; Xiaohong Pan; Qiaoyun Wang; Xue Gao; Chaoyun Wang; Xiuli Zhang; Yuxia Liu; Shucui Li; Hongliu Sun (Neuroscience Bulletin, 2020)

Trends in agricultural heat and solar radiation resources in Northeast China: A multistage spatio‐temporal analysis - Qi Hu; Feifei Pan; Xuebiao Pan; Qiuyue Li; Changxiu Shao; Zhihua Pan; Yurong Wei (International Journal of Climatology, 2016)
Climate change has changed the distribution of climate resources in crop growing season, and caused some impacts on agricultural production. Based on daily meteorological data collected at 71 meteorological stations in Northeast China, trends at multi‐temporal scales (decadal, annual, monthly, and 10‐day) and spatial patterns of heat resources [temperature, frost‐free period ( FFP )] and solar radiation resources [growing season's sunshine hour ( GSS )] are estimated over the period 1961–2012. The period of 2000–2012 has been successively warmer than the previous decades with higher mean values for both temperature and FFP , and temperature had an abrupt increasing change in the 1980s. An increasing trend was identified for the daily mean temperature in the study area, with the trend value (0.30 °C decade −1 ) double the global warming rate (0.14 °C decade −1 ). As the last frost date advanced by 1.9 days decade −1 in spring and the first frost date delayed by 1.6 days decade −1 in fall, FFP increased by 17.9 days in recent 52 years with the average trend value of 3.5 days decade −1 . Temperature in February exhibited the highest increasing rate; furthermore, the maximum temperature trends occurred in the last 10 days of February at most stations. Daily sunshine hours decreased in June, July, and August, but GSS showed small changes at decadal and annual scales because of the prolonged FFP . In summary, climate change has prolonged FFP , increased the heat resource, and slightly changed solar radiation resource during crop growing season, which is beneficial for agriculture in Northeast China.